Clinical Response to Procedural Stroke Following Carotid Endarterectomy: A Delphi Consensus Study. (September 2021) - Meershoek, Armelle J.A.; de Waard, Djurre D.; Trappenburg, Jaap; Zeebregts, Clark J.; Bulbulia, Richard; Kappelle, Jaap L.J.; de Borst, Gert J.; ,; Bonati, L.H.; Brott, T.G.; McCabe, D.; Calvet, D.; et al.
Abstract : Objective: No dedicated studies have been performed on the optimal management of patients with an acute stroke related to carotid intervention nor is there a solid recommendation given in the European Society for Vascular Surgery guideline. By implementation of an international expert Delphi panel, this study aimed to obtain expert consensus on the optimal management of in hospital stroke occurring during or following CEA and to provide a practical treatment decision tree. Methods: A four round Delphi consensus study was performed including 31 experts. The aim of the first round was to investigate whether the conceptual model indicating the traditional division between intra- and post-procedural stroke in six phases was appropriate, and to identify relevant clinical responses during these six phases. In rounds 2, 3, and 4, the aim was to obtain consensus on the optimal response to stroke in each predefined setting. Consensus was reached in rounds 1, 3, and 4 when ≥ 70% of experts agreed on the preferred clinical response and in round 2 based on a Likert scale when a median of 7 – 9 (most adequate response) was given, IQR ≤ 2. Results: The experts agreed (> 80%) on the use of the conceptual model. Stroke laterality and type of anaesthesia were included in the treatment algorithm. Consensus was reached in 17 of 21 scenarios (> 80%). Perform diagnostics first for a contralateral stroke in any phase, and for an ipsilateral stroke during cross clamping, or apparent stroke after leaving the operation room. For an ipsilateral stroke during the wake up phase, no formal consensus was achieved, but 65% of the experts would perform diagnostics first. A CT brain combined with a CTA or duplex ultrasound of the carotid arteries should be performed. For an ipsilateral intra-operative stroke after flow restoration, the carotid artery should be re-explored immediately (75%). Conclusion: In patients having a stroke following carotid endarterectomy, expedited diagnostics should be performed initially in most phases. In patients who experience an ipsilateral intra-operative stroke following carotid clamp release, immediate re-exploration of the index carotid artery is recommended.